PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Sariayu Martha Tilaar di Kota Semarang) - Nadya Calista Adriana; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2020)
Sariayu is one of the brands that creates beauty care products and has been around for decades. There are many new local product whose quality is just as good as previous products. Sariayu has a significant decrease in sales in the past year. Sariayu also didn’t occupy the position as one of the list of favorite local cosmetic brands in Indonesia for the past 3 years. This study aims to determine the effect of brand image and brand trust on purchasing decisions through buying interest as an intervening variable. This type of research is explanatory research and sampling uses nonprobability sampling techniques, purposive sampling method. Data collection using questionnaires and google form. The sample used was 100 respondents Sariayu users in the city of Semarang. This study uses quantitative analysis with validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression, significance of the t test and F test, and sobel analysis to test the effect of intervening variable. The results showed that there was a positive and significant influence on brand image and brand trust on buying interest, brand image and brand trust on purchasing decisions, and positive and significant influence of buying interest on purchasing decisions. Based on the sobel test results, buying interest can partially mediate the influence of brand image on purchasing decisions and can partially mediate the influence of brand trust on purchasing decisions. Suggestions for this research are that Sariayu further enhances the visualization of advertisements and adds variety to its products